The Relationship Between Covid-19 Vaccination And The Incidence Of Covid-19 At The Hospital Putri Hijau Hospital, Medan - Eva Sartika Dasopang; Desy Natalia Siahaan; Fenny Hasanah; Salma Handayani Lubis; Yohana Yuni M; Ramona Pane (International Journal of Health and Pharmaceutical (IJHP), 2024)
Vaccination is the process of entering vaccines to stimulate the body's immune system, as a preventive effort in reducing morbidity and mortality caused by the coronavirus. Putri Hijau Hospital in Medan City, which participated in the second dose of Covid-19 vaccination, confirmed that the respondents who were still affected by Covid-19 needed to be developed, so in particular knowing the number of cases of Covid-19 that appeared in respondents who had been infected. received a second dose of vaccination. The purpose of this study was to see whether there was a relationship between vaccination and the incidence of Covid-19 at Putri Hijau Hospital in Medan.This type of research uses a quantitative approach method by using a questionnaire distributed through the Google Form platform on a smartphone to store all the answers that have been filled in by the respondent based on the questionnaire guidelines that have been made previously with the target of respondents who have vaccinated the second dose of Covid-19.The results showed that from 100 respondents there were 28 male patients (28%) and 72 female patients (72%). Judging from the age of most patients at the age of 15 to 25 years. There were 8 people and 92 people who were not exposed. With the symptoms of Covid-19, such as fever, cough, sore throat, and loss of sense of smell. This is because the respondents had antibodies that were formed slightly after vaccination, were active outside the home, did not apply health protocols and maintained their immune system so that they were exposed to Covid-19.